Altered Expression of ACE2 and Co-receptors of SARS-CoV-2 in the Gut Mucosa of the SIV Model of HIV/AIDS - Hu, Shuang; Buser, Elise; Arredondo, Juan; Relyea, Dylan; Santos Rocha, Clarissa; Dandekar, Satya (Frontiers in Microbiology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the cause of the COVID-19 pandemic, is initiated by its binding to the ACE2 receptor and other co-receptors on mucosal epithelial cells. Variable outcomes of the infection and disease severity can be influenced by pre-existing risk factors. Human immunodeficiency virus (HIV), the cause of AIDS, targets the gut mucosal immune system and impairs epithelial barriers and mucosal immunity. We sought to determine the impact and mechanisms of pre-existing HIV infection increasing mucosal vulnerability to SARS-CoV-2 infection and disease. We investigated changes in the expression of ACE2 and other SARS-CoV-2 receptors and related pathways in virally inflamed gut by using the SIV infected rhesus macaque model of HIV/AIDS. Immunohistochemical analysis showed sustained/enhanced ACE2 expression in the gut epithelium of SIV infected animals compared to uninfected controls. Gut mucosal transcriptomic analysis demonstrated enhanced expression of host factors that support SARS-CoV-2 entry, replication, and infection. Metabolomic analysis of gut luminal contents revealed the impact of SIV infection as demonstrated by impaired mitochondrial function and decreased immune response, which render the host more vulnerable to other pathogens. In summary, SIV infection resulted in sustained or increased ACE2 expression in an inflamed and immune-impaired gut mucosal microenvironment. Collectively, these mucosal changes increase the susceptibility to SARS-CoV-2 infection and disease severity and result in ineffective viral clearance. Our study highlights the use of the SIV model of AIDS to fill the knowledge gap of the enteric mechanisms of co-infections as risk factors for poor disease outcomes, generation of new viral variants and immune escape in COVID-19.